Quality of Life and Its Relationship with Periodontal Disease: Kualitas Hidup dan Hubungannya dengan Penyakit Periodontal - Wulandari, Pitu; C Masulili, Sri Lelyati; Soeroso , Yuniarti (Dentika: Dental Journal, 2022)
Periodontal disease is an inflammatory disease of the teeth-supporting tissues which consist of the gingiva, alveolar bone, cementum, and periodontal ligament. Enlargement and bleeding gums preceding tooth loss are clinical symptoms of this disease. Moreover, early diagnosis is difficult for patients until severe destruction has occurred. The impacts include feelings of disturbance and discomfort that will affect the quality of life. Periodontal health is not only limited to relieving pain but also includes aesthetic purposes, preventing further damage, and maintaining general health. This is because dental and oral health is an integral part of general well-being, which allows individuals to achieve their most important goals, namely a better quality of life. This study aims to examine the relationship between quality of life and periodontal disease.